CSI, crime scene investigation. The complete eighth season [videorecording (DVD)] - Helgenberger, Marg; Dourdan, Gary; Eads, George, 1967-; Fox, Jorja; Szmanda, Eric; Hall, Robert David; Guilfoyle, Paul (CSI, crime scene investigation (Television program), 2008)
Sara is kidnapped by the miniature killer; the parents of a missing girl are murdered and the suspect is a pastor; a popular movie actress is murdered; a young boy and his babysitter are murdered and FBI agent Jack Malone comes to investigate; a well-known Vegas humanitarian is killed for her involvement in a dog-fighting ring; the team investigates the death of a young girl left in a cardboard box; Warrick is found at a mobster's crime scene with a murder weapon.